2000
DOI: 10.1103/physrevb.62.2605
|View full text |Cite
|
Sign up to set email alerts
|

Laterally coupled few-electron quantum dots

Abstract: We present ground-state calculations for laterally coupled quantum dots containing 2, 4, and 8 electrons. As our emphasis is on spin effects our results are obtained by applying spin-density functional theory (SDFT). By varying the distance between the centers of the coupled quantum dots, the transition from weak to strong coupling situation is realized. For the 2-electron system we also apply the Heitler-London approximation and analytical concepts to check the reliability of SDFT calculations in this case. I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
74
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 23 publications
1
74
1
Order By: Relevance
“…It can further be concluded that the spontaneous polarization and ferromagnetic ordering predicted for weakly-coupled double QD's in Refs. [13,14] is an artifact of the molecular-orbital structure implicit [32] in the framework of LSD calculations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It can further be concluded that the spontaneous polarization and ferromagnetic ordering predicted for weakly-coupled double QD's in Refs. [13,14] is an artifact of the molecular-orbital structure implicit [32] in the framework of LSD calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we show that the onset at a moderate interdot barrier or interdot distance d 0 , as well as the permanency for all separations d > d 0 , of spontaneous magnetization and ferromagnetic ordering predicted for Double QD's by local-spin-density (LSD) calculations [13,14] is an artifact of the MO structure implicit in the framework of these density-functional calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As our theory is based on a sophisticated quantum chemistry approach [26], our results should have general qualitative and semi-quantitative validity. There have been several recent theoretical calculations of the ground state spin polarization properties of multielectron quantum dot systems using the density functional theory [27][28][29]. For the purpose of quantum computation of interest to us in this paper, however, the knowledge of the excited states is crucial in determining whether a particular number of electrons can serve as an effective qubit-in particular, we need an accurate evaluation of the singlet-triplet energy splitting in the system.…”
mentioning
confidence: 99%
“…As noted by previous research 4,5,10 , one of the most attractive setup among fewparticle lateral quantum dots is the two-electron case in which the singlet and triplet states can be tuned to be bound into a fourfold degenerate ground state or, depending in the double QD parameters, artificially introducing an energy gap between the singlet and triplet states. This particular characteristic is very similar to that already observed in a two-minima QD subjected to a magnetic field 6 .…”
mentioning
confidence: 99%